1979
DOI: 10.1055/s-0029-1231358
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung der Mastalgie in der Mammadiagnostik

Abstract: Of 700 women on whom mammograms were carried out for various indications, more than half complained of mastalgia. A quarter of the women had suffered frequently from diffuse breast pain, and one third complained of mastaglia. A quarter of the women had suffered frequently from diffuse breast pain, and one third had had pain for years. One third complained of local breast pain. Changes in the mammogram amongst women with diffuse breast pain were no more common than in women without symptoms. There was no correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Severe cyclical mastalgia may be seen in women whose breasts are normal or moderate to heavy fibroadenotic (Bischoff and Wenderlein 1979). demonstrated that women suffering from cyclical mastalgia and well developed diffuse fibroadenosis have slightly, but significantly elevated basal serum prolactin concentrations compared to normals.…”
Section: Introductionmentioning
confidence: 98%
“…Severe cyclical mastalgia may be seen in women whose breasts are normal or moderate to heavy fibroadenotic (Bischoff and Wenderlein 1979). demonstrated that women suffering from cyclical mastalgia and well developed diffuse fibroadenosis have slightly, but significantly elevated basal serum prolactin concentrations compared to normals.…”
Section: Introductionmentioning
confidence: 98%